x-55=10

Simple and best practice solution for x-55=10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-55=10 equation:


Simplifying
x + -55 = 10

Reorder the terms:
-55 + x = 10

Solving
-55 + x = 10

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '55' to each side of the equation.
-55 + 55 + x = 10 + 55

Combine like terms: -55 + 55 = 0
0 + x = 10 + 55
x = 10 + 55

Combine like terms: 10 + 55 = 65
x = 65

Simplifying
x = 65

See similar equations:

| 2q^3-5q^2-500=0 | | 42-n*n=n | | 1996+43x=0 | | log(10)x+log(10)x-1=log(10)30 | | -24+11=5x+3-4x | | .10(c+3)=-12 | | log(x)+log(x-1)=log(30) | | 21-x=28 | | n-n*n=72 | | 4(a+9)=7[a-(3-a)] | | 9x^2=50x-25 | | 4x-7=36 | | x^3-5x^2+4x-2=0 | | 42x=35x+70 | | 6(4n-4)=-60 | | 8-2n=40 | | 7x+7=-5x+43 | | 49s^2-14s+1=0 | | 8k^2-20=-9k | | 5(7+2)=x-11 | | x-0.4=4.2 | | f(x)=ln(6x) | | 4x+5y+4=0 | | Cos(5x)-cos(3x)=0 | | .2x+13+x=-.10(x+40)+4 | | 10-3(3-2)=8 | | 42r^2=56-r | | (p+6)(p-2)=-7 | | x-1.2-2=-5 | | 144=[2x] | | 2r^2+19r=-24 | | 3s^2+8s=3 |

Equations solver categories